Effects of being harmed or observing the harm on others in university students - Galguera Rosales, Ricardo (2021)
Background: Based on the characterization of harmful behaviors, understood as preventing others the fulfillment of their behavioral criterion. Objectives: This study aimed to evaluate the effect of different harm distributions and amounts regarding the choice of harming others or not. Method: An A-B design was used with a baseline and an experimental phase. Thirty-five (35) higher education students participated in the study. They were selected through a non-probability convenience sampling and randomly assigned to one of the seven study groups or a control group. Such study groups differed from each other by the type of harm distribution –i.e., received or observed– and the number of harm notifications –i.e., 1, 5 and 15–. The task was to solve arithmetic operations wherein the participation of three students was simulated. Said simulated students’ role could be to harm or be harmed, according to the group they belonged to. Results: The results indicate a significant differential effect among the distributions. Additionally, a tendency towards reciprocity was shown when someone was harmed, which was directly proportional to the harm amount. Conclusions: It is concluded that there are multifactorial emergency conditions of harmful behaviors, including the identification of the person who harms others, the score, the moment and the harmed person Authorship contribution RGR: contributed with the conception of the study and the programming of the task. He carried out the supervision of the study instrumentation, data collection, statistical analysis and proposed the general structure of the manuscript. APH: contributed with the formal invitation to study participants, data collection and statistical analysis. She reviewed and revised the manuscript. ARH: contributed with the formal invitation to the study participants, supervision of the study instrumentation, as well as data collection and data entry. She carried out the revision and modification of the manuscript. ERH: contributed to the conception of the study and discussion of the design. She carried out the review and modification of the final manuscript. HOSV: contributed with the discussion of the study design, as well as with the design and elaboration of the task to be performed. Carried out the final revision of the manuscript.